2018
DOI: 10.1136/sextrans-2018-053639
|View full text |Cite
|
Sign up to set email alerts
|

Neighbourhoods, networks and pre-exposure prophylaxis awareness: a multilevel analysis of a sample of young black men who have sex with men

Abstract: ObjectiveYoung black men who have sex with men (YBMSM) in the USA represent a subgroup that has the highest HIV incidence among the overall population. In the USA, pre-exposure prophylaxis (PrEP) is an effective prevention intervention to prevent HIV acquisition when taken regularly. Neighbourhood and network factors may relate to PrEP awareness, but have not been studied in YBMSM. This study aimed to examine the relationship of neighbourhood and network characteristics with PrEP awareness among YBMSM.MethodsW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 29 publications
1
17
0
1
Order By: Relevance
“…As such, neighborhood contexts and network characteristics may influence one’s risk for HIV infection, as well as HIV-related prevention and care behaviors. There is a growing literature that has identified several salient neighborhood and network determinants of HIV-related outcomes among MSM [17,18,19,20]. First, physical characteristics of the built environment, such as the absence of public transportation infrastructures, may define and limit access to HIV prevention and care services [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…As such, neighborhood contexts and network characteristics may influence one’s risk for HIV infection, as well as HIV-related prevention and care behaviors. There is a growing literature that has identified several salient neighborhood and network determinants of HIV-related outcomes among MSM [17,18,19,20]. First, physical characteristics of the built environment, such as the absence of public transportation infrastructures, may define and limit access to HIV prevention and care services [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…15 Similarly, another study found that PrEP awareness among young Black gay and bisexual men related both to their networks and also the density of health clinics in their home neighbourhoods. 16 The degree to which any of these relationships are relevant to transgender women of colour, however, remains unknown, especially given the tendency of previous research to conflate populations of transgender women with those of cisgender gay and bisexual men. 17 18 Further, research that permits causal inferences and accounts for the complexities of network and neighbourhoods is lacking; the existing literature, nevertheless, highlights the necessity of attending to network and neighbourhood predictors of PrEP uptake.…”
Section: Open Accessmentioning
confidence: 99%
“…PrEP-utilizing peer navigators may help combat medical mistrust and fill in PrEP-related knowledge gaps that exist among minority MSM [17][18][19][20]. For example, in a cohort of young Black MSM in Chicago, discussions with confidants regarding HIV prevention were associated with greater PrEP awareness (aOR = 2.26, 95% CI 1.00 to 5.09) [21]. Peer navigator interventions targeting the HIV care cascade demonstrate that peers can improve patient engagement and increase medication adherence [22].…”
Section: Introductionmentioning
confidence: 99%